UPAYA PEMERINTAH KABUPATEN ROKAN HULU DALAM MENINGKATKAN PAD (PENDAPATAN ASLI DAERAH) MELALUI WISATA RELIGI ISLAMIC CENTRE DI ROKAN HULU TAHUN 2018 - 2022 - Ibnu Ulya. S; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Tourism is an industry that is able to provide rapid economic growth for a country. The purpose of this research is to find out the efforts made by the Government of Rokan Hulu Regency in increasing local revenue (PAD) through the Islamic Center religious tourism as well as the driving and inhibiting factors. This study uses a qualitative approach, located in the Government of Rokan Hulu Regency, Riau Province. The subjects in this study were the Management Board of the Grand Mosque Islamic Center of Rokan Hulu Regency and BAPENDA (Regional Revenue Agency) of Rokan Hulu Regency. While the object of this study is the Islamic Center religious tourism in Rokan Hulu Regency. Documentation data collection techniques, observations and interviews. As well as data analysis methods using descriptive qualitative. The results of the study explain the efforts made by the government of the Rokan Hulu Regency in increasing local revenue (PAD) through religious tourism Islamic centers ncluding increasing attractiveness such as different nuances of prayer, having architecture decorated with various calligraphy, having a tower that symbolizes asmaul husna . Improved manageability with messages and persuasion. The facilities provided include prayer facilities, mosque management facilities and supporting facilities. While the infrastructure provided includes the provision of accommodation, increased access to transportation, facilities such as restaurants, supermarkets, places to sell souvenirs and health clinics. Factors include increasing existing attractions such as building a building concept that can be combined with Islamic values and roviding supporting facilities. While the inhibiting factors encountered include limited funds or budget provided, lack of competent human resources and facilities and infrastructure that are still not optimal. Keywords: Regional Original Income (PAD), Religious Tourism